"You get to know the people and whether they're talking sense or not": Negotiating trust on health-related forums. (August 2016) - Brady, Ellen; Segar, Julia; Sanders, Caroline
Abstract: The internet is increasingly being used as a source of health advice and information by individuals with long term conditions (LTCs). Specifically, online forums allow people to interact with others with similar conditions. However, it is not clear how online health information is assessed by those with LTCs. This study aims to address this gap by exploring how individuals with contested and uncontested LTCs utilise internet forums. Semi-structured interviews were conducted with 20 participants with ME/CFS and 21 participants with type 1 and 2 diabetes and analysed using thematic analysis. Participants were recruited via online and offline routes, namely forums, email lists, newsletters, and face-to-face support groups. The findings indicate that the use of online forums was a complex and nuanced process and was influenced by a number of individual and illness-specific factors. Participants trusted those with similar experiences and perspectives as themselves, while also valuing conventional biomedical information and advice. By accessing support online, forum users were able to draw on a personalised form of support based on the lived experiences of their peers. However, the role of digital literacy in developing and maintaining online relationships must be acknowledged. Highlights: The use of online forums by individuals with LTCs is a complex and nuanced process. Participants trust those with similar experiences and perspectives as themselves. Users can access a personalised form of support based on the experiences of peers. Role of digital literacy in developing online relationships must be acknowledged.